Acquired optociliary shunt vessels in papilloedema. Issue 4 (April 1980) - Eggers, H M; Sanders, M D
Abstract : Seven cases are presented in which prolonged papilloedema led to the development of acquired optociliary shunt vessels. These vessels may also be found with optic nerve tumours, particularly spheno-orbital meningiomas, optic nerve drusen, glaucoma, and after central retinal vein occlusion. Two patients had intracranial tumours, 4 benign intracranial hypertension, and one Crouzon's disease. Three had marked atrophic changes of the disc. The pathophysiology of the disc changes is discussed. The triad of long-standing poor vision, acquired optociliary shunts, and optic atrophy with blurred disc margins should not be regarded as specific for spheno-orbital meningioma.